Studies On Modified Gladiolus Starch - Department of Pharmaceutics (The Nigerian Journal of Pharmacy, 2003)
Gladiolus starch was modified by the action of heat to produce two batches at pyrodextrins. The produced pyrodextrins were subjected to some pharmacopoeial tests for identitication, and some physicotechnical tests designed to establish their possible relevance in certain pharmaceutical formulations. Such parameters as microscopy, density, solubility, moisture content, reducing sugar content, surface tension at 2.5% w/v solution and rheological properties were evaluated. The result ot the physicotechnical properties indicated that these two pyrodextrins could be a versatile pharmaceutical tabletting aid, possessing multitunctionatity.